Beginning Joomla! 2nd Edition - Rahmel, Dan (Apress, 2012)
This book will guide you through nearly every aspect of the Joomla system, from basic deployment to writing your own extensions. By the time you’ve reached the last page, you’ll be able to make Joomla do almost anything that a manually designed web site can do—and in a fraction of the time. Before we get started, let’s take a quick glance at what makes Joomla such as revolutionary technology. The sections that follow describe the advantages of using a content management system (CMS) like Joomla, in addition to the features and benefits that make Joomla a compelling choice.